1999
DOI: 10.1073/pnas.96.22.12935
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic origin of conjugated double bonds: Production of fatty acid components of high-value drying oils in transgenic soybean embryos

Abstract: Vegetable oils that contain fatty acids with conjugated double bonds, such as tung oil, are valuable drying agents in paints, varnishes, and inks. Although several reaction mechanisms have been proposed, little is known of the biosynthetic origin of conjugated double bonds in plant fatty acids. An expressed sequence tag (EST) approach was undertaken to characterize the enzymatic basis for the formation of the conjugated double bonds of ␣-eleostearic (18:3⌬ 9cis,11trans,13trans ) and ␣-parinaric (18:4⌬ 9cis,11t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
142
3
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(152 citation statements)
references
References 23 publications
(31 reference statements)
4
142
3
1
Order By: Relevance
“…The oleic acid content appeared to be fairly constant in all varieties. Regarding the polyunsaturated fatty acids, α-eleostearic acid was the major one, its average percentage being 51.80, which was lower than the value 65% detected by Cahoon et al (1999) with the same seed oil. GLC data also indicated that karela seed oils contained mainly unsaturated fatty acids 72.60-74.95%, while saturated fatty acids detected represented 25.05-27.40%.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…The oleic acid content appeared to be fairly constant in all varieties. Regarding the polyunsaturated fatty acids, α-eleostearic acid was the major one, its average percentage being 51.80, which was lower than the value 65% detected by Cahoon et al (1999) with the same seed oil. GLC data also indicated that karela seed oils contained mainly unsaturated fatty acids 72.60-74.95%, while saturated fatty acids detected represented 25.05-27.40%.…”
Section: Resultsmentioning
confidence: 62%
“…These ratios indicate that the samples had a high content of unsaturated fatty acids, which may make them more attractive for the consumer who wishes to ingest this type of acids. Vegetable oils that contain fatty acids with conjugated double bonds, such as tung oil, are valuable drying agents in paints, varnishes, and inks (Cahoon et al 1999). Karela seed oils reported herein that are enriched in α-eleostearic acid (> 50% of the total fatty acid) possessing conjugated double bonds, are used commercially in coating materials and inks.…”
Section: Resultsmentioning
confidence: 99%
“…In the biosynthesis of conjugated linolenic acids, enzymes termed conjugases catalyze the formation of conjugated double bonds; the Z12 double bond of linoleic acid, for instance, is converted into the two E11 and E13 double bonds found in ␣-eleostearic acid (23). Recently, several plant seed cDNAs encoding conjugases have been characterized (22)(23)(24)(25). Interestingly, one such conjugase associated with the formation of the E11,Z13-diene in punicic acid (22) has been reported to exhibit both Z12 desaturation and E11,Z13-conjugation activities.…”
Section: Discussionmentioning
confidence: 99%
“…Jack) were transformed by using particle bombardment (45), and transgenic embryos were selected and propagated to maturity as described (46). Matured embryos from each independent event were analyzed by GC to verify expression of the F. moniliforme 3 desaturase, as described below.…”
Section: Methodsmentioning
confidence: 99%